PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KOMITMEN ORGANISASI, DAN PROFESIONALISME TERHADAP KINERJA MANAJERIAL BANK BUMN KOTA PALEMBANG - Pipit Fitri Rahayu (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2019)
The purpose of this study is to determine the effect of the participation in composing budget, organizational commitment, and professionalism on the performance of the BUMN Bank in Palembang. In addition, this institution is a company that also has branch offices, financial managers, operational managers, credit managers, and corporate finance such as Bank Mandiri, Bank Negara Indonesia. (BNI) and the State Savings Bank (BTN) of Palembang city which prioritizes 36 people. The sample that used is 36 people using a census is all the populations sampled. The technique to analyze data is multiple regression analysis with SPSS 21 software tools. The results of the study partially indicate that: (1) budget participation is positive and significant toward the managerial performance of Palembang City BUMN Bank, (2) organizational commitment is positive and significant toward managerial performance Palembang City BUMN Bank, and (3) professionalism that has a significant positive effect on the managerial performance of the BUMN Bank of Palembang City. And the results of the simultaneous testing also show that budget participation, organizational commitment, and professionalism have a positive and significant effect on the performance of managers of BUMN Bank Palembang City